Development of Digital Heat Expansion Learning Media Based on Arduino Uno to Improve Students' Generic Science Abilities - Pratiwi, Rosi (Pascasarjana, Mataram University, 2024)
Students are less able to develop their generic science skills, such as understanding symbols in science lessons, and many of them cannot even use measuring instruments. One way to improve this ability is to develop learning media. This research aims to develop learning media in the form of digital heat expansion based on Arduino Uno that is valid, practical and effective to improve students' generic science abilities. This research includes research and development by adopting the ADDIE development model. The product was tested at one of the state schools in West Lombok class VII. The research results show that the device validation is in the valid and reliable category. The results of observations of learning implementation with an average score of 93.46%, teacher response 98.28%, and student response 89.66% in the very practical category. N-gain is used to see the effectiveness of the product being developed and an indicator of awareness of scale in the generic ability of science is obtained which has the highest N-gain of 94%. The paired t test was used to see the difference between the pre-test and post-test in the trial class, it was found to be significant at 0.00 and it was concluded that there was an increase in generic science abilities. The conclusion obtained is that the development of digital heat expansion learning media based on Arduino Uno is feasible, very practical and effective for improving students' generic science abilities